Mesure de la qualité des services d'enseignement et restructuration des secteurs éducatifs - Annie Vinokur (Les éditions de la Maison des sciences de l'Homme, 2005)
We have seen in Normand's paper that pedagogical improvement had, historically in the USA, borrowed its quality assessment system from the industrial model of rationalisation. The same pattern is now being applied on a global scale to the evaluation of all providers of educational services. The recent increase of quality assurance, accreditation and quality management devices in education can be related both to the development of transnational labour and educational markets and to the pressures toward a new flexible and efficient governance of education systems. This contribution endeavours to show the functionality - but also the contradictions - of this movement.